PARTISIPASI MASYARAKAT PADA PROGRAM PNPM DALAM PEMANFAATAN AIR BERSIH DI DESA BUO KECAMATAN LOLODA KABUPATEN HALMAHERA BARAT - Riko Dalima; Maria Heny Pratiknjo; Mahyudin Damis (Universitas Sam Ratulangi, 2021)
Development is part of culture in an anthropological perspective. Development is the existence of a number of human actions. Meanwhile, culture is a guideline for human actions. Thus, development is oriented and aims to build the society and civilization of humanity. National development in Indonesia is carried out in order to build a Indonesian people and the development of the entire community. National development can be realize by poverty alleviation efforts either directly or indirectly through government programs.There in 2013 the government realized the Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri in order to fulfill clean water for the residents of Buo Village. With this independent PNPM, the villagers took the initiative to create a forum to hold meetings of all Buo villagers, actively participating in order to immediately overcome the shortage of clean water for decades. Buo villagers also actively build clean water shelters and pipelines to the homes of villagers. Finally, in 2013 the program was complete with the support and active participation of the community.The National Program for Community Empowerment in the utilization of clean water that is considere successful is important. Every issue discussed can be direct to create community sustainability about clean water management in Buo Village.Keywords: participation, development, clean water